Proposing a non-monetary Islamic index for poverty measurement at Lembaga Zakat Selangor (LZS), Malaysia / Mohamed Saladin Abdul Rasool - Abdul Rasool, Mohamed Saladin (2016)
In practice, most zakat organizations in Malaysia use the monetary approach in measuring poverty through the conventional Poverty Line Income (PLI) method, and recently the had al kifayah (HAK) approach was adopted by zakat institutions. The main aim of the present study is to present a multidimensional poverty measurement from an Islamic perspective as an alternative to the current monetary measurement. The study proposes an Islamic Poverty Index (IPI) which consists of non-monetary indicators comprising of maqasid-al shariah (objective of religion) elements, namely, religion, knowledge, physical self, offspring and wealth. The respondents of this cross-sectional study were recipients of zakat aid from Selangor Zakat Board (LZS), which has the highest zakat collection in Malaysia. The two main phases involved in the study are the development of a questionnaire as the research instrument and the data collection stage. An expert review was conducted to develop the questionnaire and the data collection was carried out through a survey aided by a structured questionnaire on selected heads of poor households using the proportionate sampling method in the state of Selangor, the most populated state (with the highest number of Muslims) in Malaysia. In achieving the objectives of the study, data collected from 258 respondents were analyzed using various statistical methods, namely, descriptive statistics (frequency tables and cross tabulation), comparative mean analysis (T test and ANOVA), correlation analysis and regression analysis. The results of the study revealed that there were five dimensions of IPI with thirteen indicators incorporating maqasid-al shariah principles with religion and physical self being the highest weighted dimensions, followed by knowledge, offspring and wealth. In addition, there was a significant correlation between both of the monetary dependent variables. However, PLI was not significantly correlated to both of the monetary dependent variables. The study also found out that the number of respondents who were poor in all the three poverty measurement employed in this study was relatively small. Furthermore, the determinants of each of the three dependent variables were also identified. As a summary, the proposed IP in the present study would be able to reflect the multidimensional phenomenon of poverty in a more holistic way and is expected to have an impact on zakat organizations as it gives a new perspective on measuring poverty.